The Relationship between Emotion Regulation and Social Support with Resilience of Mothers with Stunted Toddlers - Amellia , Rizky; Suroso; Farid, Muhammad (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This study aims to explore the relationship between emotional regulation, social support, and resilience among mothers of toddlers with stunting status. Mothers facing this condition often encounter high psychological pressure due to the complexities of care and concerns regarding their child's health. The research was conducted on a finite population with a sample of 40 mothers of stunted toddlers. Measurement instruments included the Resilience Questionnaire Test (RQ-TEST), the Emotion Regulation Questionnaire (ERQ), and the Social Support Scale (SSS), analyzed using Spearman's rho correlation analysis.The results indicated a significant positive relationship between emotional regulation and resilience (rho = 0.350, p < 0.05). Higher emotional regulation was associated with higher resilience among mothers. The study also found a significant positive relationship between social support and resilience (rho = 0.517, p < 0.05). Greater social support was linked to higher levels of resilience in mothers. However, the study has limitations due to the small sample size and potential response bias in data collection methods. Future research is recommended to expand the sample and use more varied data collection methods to enhance the validity of the results.The implications of this study suggest that interventions to improve emotional regulation and social support could effectively enhance the resilience of parents in facing the challenges of caring for toddlers with stunting status, potentially yielding significant positive impacts on the well-being of affected families.